EDUCATION MARKETING MANAGEMENT STRATEGIES: USES THE LITERATURE RESEARCH METHODS - Anwar Ebtadi (RADJA PUBLIKA, 2023)
The purpose of this research is to examine marketing management methods in educational institutions in Indonesia. Marketing management is an effort to compile planning and implementation that involves directing activities, organizing, coordinating, controlling, and holding marketing activities in an institution to achieve an institution's objectives effectively and efficiently, which is often referred to in terms of management objectives. Marketing and marketing strategy are associated as the primary tools for achieving company goals, increasing sustainable competitive advantage through market entry, and serving target markets through the application of preset marketing variables. Educational marketing, which can be gained through promotion, serves to inform the public about school products. Increasing public interest in school products, emphasizing the contrasts between school products and other school products. This study's research method is a literature review in a scientific study, is something that is required in the overall approach of research procedures. Literature research, also known as literature study, is an activity that involves combining data in accordance with scientific works that serve as the goal of research, as well as gathering data in the form of literature or studying and solving problems using relevant literature materials. Based on the findings of the studies, it is possible to conclude that marketing management strategies are required to develop and promote an educational institution to the larger community in order to make it easier for the public to choose and understand the quality of the educational institution offered.